Red cell distribution width is associated with short‐term mortality in critically ill patients with heart failure. (29th June 2022) - Zhang, Xinyu; Wang, Yi; Chen, Naiyi; Liu, Yan; Xiao, Jie; Lin, Zongwei; Lu, Huixia; Ji, Xiaoping
Abstract: Aims: There is limited evidence for the correlation between short‐term mortality and red cell distribution width (RDW) in critical patients with heart failure. Herein, a retrospective cohort study was conducted to investigate whether RDW was independently associated with short‐term mortality in critically ill patients with heart failure. Methods and results: As a retrospective cohort study, it involved a total of 9465 patients with heart failure from the MIMIC‐IV database. The target‐dependent and independent variables were in‐hospital mortality, 90 day mortality and RDW measured at baseline, respectively. The relationship between all‐cause death and baseline RDW in hospital and after 90 days of admission to ICU was evaluated by using the Kaplan–Meier plot and Cox proportional hazard analysis. The average age of participants was 74.4 (64.2, 83.5) years old, among whom about 54.6% were male. Results of the adjusted Cox proportional hazard model revealed that RDW had a positive association with both in‐hospital and 90 day mortality risk after the adjustment of confounders (HR = 1.09, 95% CI: 1.04–1.15, P  < 0.001; HR = 1.11, 95% CI: 1.08–1.14, P  < 0.001, respectively). A non‐linear relationship was found between RDW and 90 day mortality, which had a threshold of 14.96%. The effect sizes and confidence intervals below and above the threshold were 1.36 (1.14 to 1.62) and 1.09 (1.04 to 1.15), respectively. It was also found by subgroup analysis that there were stronger correlations in male and patients with normal renal function. Conclusions: Our data suggest that the short‐term mortality of critically ill patients with HF is independently predicted by RDW. At the same time, large prospective research and longer follow‐up time are required to further validate the findings of this study.